Pengaruh Beban Kerja dan Lingkungan Kerja Terhadap Kinerja Karjawan Distrik Sorong Utara - Irene Yuliana Edowai; Edward Clan; Andre Maryen (Journal on Education, 2023)
The influence of excessive workload can create an uncomfortable working atmosphere for workers. Excessive work load can trigger the emergence of work stress more quickly. On the other hand, a lack of workload can cause losses for the organization/agency. This is because the responsibilities given by the government for the work do not match the abilities possessed by the workers, which can result in errors in financing the work of employees in the North Sorong District. Problems that occur due to the varying characteristics of the human resources they have and the mismatch between the workload and the capabilities of the human resources can result in the work being given to be of poor quality. Based on this problem, the researcher defines and uses the title "The influence of work environment workload on employee performance North Sorong District. This study uses a quantitative approach. Data obtained in the field is in the form of quantitative data, according to Sugiyono, is data that is processed from research results in the form of numbers, where the quantitative approach is the acquisition of data from various sources of information that is relevant to the problem being researched and is related to proof of the concept/theory used. For the work environment North Sorong District employees include equipment, work facilities and work relations. The equipment in the North Sorong District is complete manually and the existing facilities regarding the work relations in the North Sorong District are well established.